On Happiness in Teaching: An Ordered Logit Modeling Approach - Casinillo, Emily L; Casinillo, Leomarich F; Casinillo, Maita F (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
This study was conducted to explain the degree of happiness in teaching and determine its influencing socio-economic factors. Using a probabilistic sampling method, the study employed 127 junior and senior high school teachers as respondents. Primary data were collected through developed questionnaires and analyzed using descriptive measures and ordered logit modeling. Results showed that this study documented a statistically significant determinant of the feeling of happiness in teaching, namely: other sources of income, creative and enjoyable teaching experience, school compound, social relationship, and health condition. Having other sources of income has an inverse effect on the happiness of teachers, this might be due to additional responsibilities while serving the students. The study showed that teachers are more likely happy if they found their job as creative and enjoyable which positively influences their well-being and professional growth. There is also a higher chance of being happy if the school environment is conducive for learning and provides comfort to teachers. Furthermore, being socially oriented and the healthy teacher are productive and efficient in work which is more likely to be happy.